2016
DOI: 10.1021/acs.nanolett.5b04664
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus–Zinc Oxide Nanomaterial Heterojunction for p–n Diode and Junction Field-Effect Transistor

Abstract: Black phosphorus (BP) nanosheet is two-dimensional (2D) semiconductor with distinct band gap and attracting recent attention from researches because it has some similarity to gapless 2D semiconductor graphene in the following two aspects: single element (P) for its composition and quite high mobilities depending on its fabrication conditions. Apart from several electronic applications reported with BP nanosheet, here we report for the first time BP nanosheet-ZnO nanowire 2D-1D heterojunction applications for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 42 publications
(165 reference statements)
3
138
0
2
Order By: Relevance
“…Indeed, several research groups have demonstrated hybrid phototransistors based on 0D-2D heterojunctions of PbS QDs and graphene, MoS 2 , or WSe 2 . [30] In this study, we present a mixed-dimensional 1D ZnO NW (n-type)-2D WSe 2 nanosheet (p-type) vdW heterojunction device for spectral photodetection as well as imaging process. [29] However, although 1D ZnO metal oxide semiconductor NWs are also a promising candidate for mixed-dimensional vdW heterostructures, 1D ZnO NW-2D vdW material heterojunctions have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several research groups have demonstrated hybrid phototransistors based on 0D-2D heterojunctions of PbS QDs and graphene, MoS 2 , or WSe 2 . [30] In this study, we present a mixed-dimensional 1D ZnO NW (n-type)-2D WSe 2 nanosheet (p-type) vdW heterojunction device for spectral photodetection as well as imaging process. [29] However, although 1D ZnO metal oxide semiconductor NWs are also a promising candidate for mixed-dimensional vdW heterostructures, 1D ZnO NW-2D vdW material heterojunctions have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Since the first isolation of black phosphorus and demonstration of a field effect device, numerous reports investigating the synthesis and optoelectronic properties of this material have emerged, appropriately summarized in recent reviews. 5,6,[10][11][12] Likewise a number of reports have also appeared on the applications of black phosphorus in fast photodetectors 13 , polarization sensitive detectors, 14 waveguide integrated devices 15 , multispectral photodetectors 16 , visible to near-infrared absorbers 17 and emitters, [18][19][20][21] heterojunction 22 and split gate p-n homojunction photovoltaics 23 , gatetunable van der Waals heterojunctions for digital logic circuits 24,25 and gigahertz frequency transistors in analog electronics 26 . A majority of the studies on both the fundamental optical properties of black phosphorus and applications in optoelectronic devices have explored only the visible frequency range [27][28][29][30] .…”
mentioning
confidence: 99%
“…[12] Recent studies of 2D materials [13] have revealed a variety of 2D semiconductors (2DSCs) with excellent electronic properties [14][15][16][17] and ultrathin body thickness. However, despite several studies on 2DSCs based JFETs reported to date, [23][24][25][26] the SS achieved in these devices remain > 100 mV dec −1 , far from the ideal value of 60 mV dec −1 . [11] Additionally, the dangling bond free van der Waals (vdW) interface formed by 2DSCs could feature a trapping free interface to promise nearly ideal junction characteristics.…”
Section: Doi: 101002/adma201902962mentioning
confidence: 90%